Development of culture inoculum for scale-up production of citric acid from oil palm empty fruit bunches by Aspergillus niger - Alam, Md. Zahangir; Bari, Md. Niamul; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (2011)
An extensive study on fungal inoculum was carried out to develop an effective culture (broth) inoculum for citric acid production from oil palm empty fruit bunches through solid state bioconversion. The effect of spores age, storage time of spore suspension inoculum, doses of spore suspension inoculum to prepare culture inoculum, ages of culture inoculum and doses of culture inoculum (concentration of biomass) on citric acid production were evaluated. It was found that the optimum age of spore was 3-4 days for the preparation of spore suspension inoculum and the maximum storage time of spore suspension inoculum was 2 days. Furthermore, the optimum dose of spore suspension inoculum was 20% (v/v) to prepare culture (broth) inoculum. The culture inoculum of 48 hrs age with biomass concentration of 0.82±0.3 g/L showed the highest production of citric acid compared to other percentage of spore suspension inoculum and culture age for all doses of culture inoculum. The highest production of citric acid of 367.4±2 g/kg-EFB was obtained with 25% (v/w) (0.21 g biomass/kg substrate) culture inoculum after 7 days of bioconversion.